Dietary exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) induces oxidative damage promoting cell apoptosis primarily via mitochondrial pathway in the hepatopancreas of carp, Cyprinus carpio - Xin Zhang; Yujie Huang; Lei Yang; Shuhuang Chen; Youlian Liu; Ni Tang; Zhiqiong Li; Xiaoli Zhang; Liangyu Li; Defang Chen (Ecotoxicology and Environmental Safety, 2024)
To investigate the mechanisms of BDE-47 on hepatotoxicity in fish, this study examined the effects of dietary exposure to BDE-47 (40 and 4000 ng/g) on carp for 42 days. The results showed that BDE-47 significantly increased carp’s condition factor and hepatosomatic index. Pathological results revealed unclear hepatic cord structure, hepatocytes swelling, cellular vacuolization, and inflammatory cell infiltration in the hepatopancreas of carp. Further investigation showed that ROS levels significantly increased on days 7, 14, and 42. Moreover, the activities of antioxidant enzymes SOD, GSH, CAT, and GST increased significantly from 1 to 7 days, and the transcription levels of antioxidant enzymes CAT, Cu-Zn SOD, Mn-SOD, GST, and GPX, and antioxidant pathway genes Keap1, Nrf2, and HO-1 changed significantly at multiple time-points during the 42 days. The results of apoptosis pathway genes showed that the mitochondrial pathway genes Bax, Casp3, and Casp9 were significantly upregulated and Bcl2 was significantly downregulated, while the transcription levels of FADD and PERK were significantly enhanced. These results indicate that BDE-47 induced oxidative damage in hepatopancreas, then it promoted cell apoptosis mainly through the mitochondrial pathway. This study provides a foundation for analyzing the mechanism of hepatotoxicity induced by BDE-47 on fish.